The Ability of Nutrient Antioxidants to Influence Oxidative Stress and Lower the Dose of Prednisolone in Patients with Alopecia Areata - N. Al- Jaff, Ashwaq; A.Humadi, Salim; A. Wohaieb, Saleh. (Iraqi Journal of Pharmaceutical Sciences, 2017)
Alopecia areata is a common disorder, hypothesized to be autoimmune in etiology. Cortisone taken orally may stimulate new hair growth. Prednisone (orally administered steroid (has proved effective for patients with alopecia areata, but its potential side effects include weight gain, metabolic abnormalities, acne and menstrual problems. This clinical study was designed to assess the clinical significance of the nutrient antioxidants (vitamin A, vitamin E and vitamin C) in reducing the dose of corticosteroids (prednisolone), and as a consequence, their side effects in patient with alopecia. The results of this study reveal the potential clinical significance of the therapy for two months with these antioxidants in reducing the dose of prednisolone from 100mg to 10 mg administered each other day and improving the rate of hair growth by attenuating free radicals damaging effect on immune system, thereby decreasing the immune complex deposition. According to the results of this study, the use of nutrient antioxidants may have an important role in protecting the immune system, and decreasing the dose and side effects that result from the use of high dose of corticosteroids.